Breeds Characterization in Three Turkish Laying Chicken Breeds Based on Egg Characteristics - Widya Pintaka Bayu Putra; Muhammad Ridho; Ilyas Nugraha (Indonesian Journal of Agricultural Research, 2021)
Breeds characterization can be performed based on their phenotypic traits. In poultry, the breeds characterization can be performed based on the egg characteristics. This study was carried out to characterize three Turkish laying chicken breeds (30-49 weeks of age) of White Leghorn (WL), Lohmann Brown (LB) and Ataks (AT) based on their characteristics. Total of 90 new stock eggs (30 eggs/breed) from Görukle market, Bursa city, Republic of Turkey were used for analysis. Three statistical analyses of principal component analysis (PCA), canonical discriminant analysis (CDA) and hierarchical cluster analysis (HCA) analysis were used for breeds characterization. According to egg size index, most of eggs in this study had normal size type. The highest coefficient of correlation (0.99) value was showed between egg weight (EW) and specific gravity (SG). The PCA revealed that four principal components (4PC’s) of egg characteristics capable to explain the total variance of egg characteristics in WL and LB hens about 83.10% and 78.95% respectively. Meanwhile, 3PC’s of egg characteristic in AT were explained about 81.70% of total variance in egg characteristics. The Euclidean distance revealed that LB and AT hens were grouped into similar cluster and WL hen was grouped into different cluster. In conclusion, the egg characteristics in birds study can be used to characterize of WL (73.3%), LB (93.0%) and AT (76.7%) hens.